2012
DOI: 10.1097/fjc.0b013e31824d4d75
|View full text |Cite
|
Sign up to set email alerts
|

Pinacidil Pretreatment Improves Vascular Reactivity After Shock Through PKCα and PKC[Latin Small Letter Open E] in Rats

Abstract: We investigated the beneficial effect of pinacidil pretreatment on vascular reactivity, calcium sensitivity, and animal survival after hemorrhagic shock, its relationship to protein kinase Cα (PKCα), protein kinase Cε (PKCε), and adenosine. Using hemorrhagic shock rats, the protective effects of different extents of pinacidil pretreatment on vascular reactivity and in which the roles of PKCα, PKCε, and adenosine were observed. Pinacidil pretreatment significantly improved shock-induced decrease of vascular rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Refractory hypotension due to vascular hyporeactivity to catecholamine is a major cause of death in severe trauma, shock, or sepsis (20,25,29). It has long been known that under these pathological conditions, AVP still has systemic vasoconstrictor and vasopressor effects (3,4,17,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refractory hypotension due to vascular hyporeactivity to catecholamine is a major cause of death in severe trauma, shock, or sepsis (20,25,29). It has long been known that under these pathological conditions, AVP still has systemic vasoconstrictor and vasopressor effects (3,4,17,24).…”
Section: Discussionmentioning
confidence: 99%
“…Protein kinase C (PKC) constitutes a family of serine/threonine kinases that serve as central signaling molecules and regulators of multiple cellular processes (5). Our previous study demonstrated that both ROCK and PKC play critical roles in the regulation of vascular reactivity (reflected by norepinephrine-induced vasoconstriction) after hemorrhagic shock (15,16,29). Furthermore, we found that AVP enhances the vasoconstrictive effect of norepinephrine via the ROCK and PKC pathways (30,32).…”
mentioning
confidence: 95%
“…In a previous study, pinacidil prevented subarachnoid hemorrhage-induced vasospasm by the restoration of large-conductance Ca 2+ -activated K + channel activities (3). Furthermore, pinacidil pre-treatment was able to exert significant protective effects following hemorrhagic shock, mainly by the activation of protein kinase C (PKC)α and PKCε via adenosine receptor A1, which restored vascular reactivity and calcium sensitivity and influenced the success of hemorrhagic shock therapy (4). Pinacidil was also demonstrated to enhance the survival of cryopreserved human embryonic stem cells (hESCs) (5).…”
Section: Introductionmentioning
confidence: 99%
“…Following plating of thawed hESCs, pinacidil significantly enhanced cell attachment capacity. Previous studies have focused on investigating the function of pinacidil in the heart and coronary artery in order to elucidate the mechanism underlying its protective effects (4). It was hypothesized that the activation and opening of the mito-KATP (6) and the sarcolemmal KATP channel (7) may be beneficial in the restoration of mitochondrial energy metabolism by closing the mitochondrial transition pore (MTP), which stabilizes the mitochondrial membrane potential (MMP) and reduces intracellular Ca 2+ levels (8).…”
Section: Introductionmentioning
confidence: 99%